2018
DOI: 10.1002/adma.201802396
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen‐Vacancy and Surface Modulation of Ultrathin Nickel Cobaltite Nanosheets as a High‐Energy Cathode for Advanced Zn‐Ion Batteries

Abstract: The development of high-capacity, Earth-abundant, and stable cathode materials for robust aqueous Zn-ion batteries is an ongoing challenge. Herein, ultrathin nickel cobaltite (NiCo O ) nanosheets with enriched oxygen vacancies and surface phosphate ions (P-NiCo O ) are reported as a new high-energy-density cathode material for rechargeable Zn-ion batteries. The oxygen-vacancy and surface phosphate-ion modulation are achieved by annealing the pristine NiCo O nanosheets using a simple phosphating process. Benefi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
347
2
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 556 publications
(375 citation statements)
references
References 51 publications
16
347
2
2
Order By: Relevance
“…In the meantime, the peak intensity of OH bond (532.8 eV) of N‐MnO 2– x @TiC/C sample is higher than that of MnO 2 @TiC/C owing to the increased surface‐absorbed water. This indicates that the surface of N‐MnO 2– x @TiC/C sample becomes more active and accessible to soak electrolyte to participate in reactions . Further evidence is provided by the EPR spectra measured at room temperature.…”
Section: Resultsmentioning
confidence: 83%
“…In the meantime, the peak intensity of OH bond (532.8 eV) of N‐MnO 2– x @TiC/C sample is higher than that of MnO 2 @TiC/C owing to the increased surface‐absorbed water. This indicates that the surface of N‐MnO 2– x @TiC/C sample becomes more active and accessible to soak electrolyte to participate in reactions . Further evidence is provided by the EPR spectra measured at room temperature.…”
Section: Resultsmentioning
confidence: 83%
“…It found that oxygen vacancy could act as a shallow donor to improve electrical conductivity of metal oxide, and serve as active sites for electrode reactions. Therefore, the optimized P‐NiCo 2 O 4− x nanosheets electrode has the advantages of the improved conductivity and enhanced concentration of active site, thus significantly improving the capacity and rate performance of the material …”
Section: Defect Engineering On Electrode Materialsmentioning
confidence: 99%
“…Nowadays, energy storage devices (ESDs) are playing a crucial role in smart electronics and wearable textiles. Rechargeable batteries (including Li, Na, K, Zn‐ions) as well as supercapacitors are being considered as promising energy storage devices for sustainable development of smart electronics . While batteries are known for their high energy density, the cycle life and charging/discharging rate are unfavorable in most cases .…”
Section: Introductionmentioning
confidence: 99%